Fabrication and Characterization of a Novel Berberine-oleanolic Acid Delivery Collagen I scaffold. (September 2020) - Chen, Zongming; Li, Yongsheng; Dai, Yao; Zhou, Zheng; Hu, Yibing; Liu, Hairong
Abstract: Postoperative bacterial infection greatly threatens prognosis of patients following tissue engineering implantation and surgical operation. In this study, a novel antibacterial tissue engineering porous scaffold has been prepared, by blending a newly synthesized berberine-oleanolic acid (HL-9) with collagen (COL I) via freeze-drying. It showed that the HL-9 delivery COL I scaffolds displayed a uniform porous three-dimensional structure, high porosity and good water absorption. These HL-9 delivery COL I porous scaffolds (HL-9/COL I scaffolds) are able to release HL-9 steadily for 15 days. HL-9/COL I scaffolds, which contains, 4% and 5% HL-9 respectively, exhibited a similar antibacterial activity against Gram-positive and Gram-negative bacteria. Hence, the HL-9/COL I scaffolds containing 3% HL-9 is used to test the biocompatibility. By employing Alamar Blue assays and FDA staining, the proliferation of MG-63 cultured with 3%HL-9/COL I scaffolds is similar with that cultured with COL I scaffolds. In conclusion, the 3%HL-9/COL I scaffolds showed a good biocompatibility and antibacterial activity, suggesting that it may be applied in tissue engineering in the future.